PENGARUH MOTIVASI DAN SIKAP TERHADAP LOYALITAS KONSUMEN PADA STUDIO JONAS PHOTO - Yuliawati, Yupi (Universitas Pendidikan Indonesia, 2016)
This study aimed to determine the effect of motivation and attitude towards customer loyalty Jonas photo studio. The research method used is descriptive verification. The findings stated motivations and attitudes affect the loyalty simultaneously and partiallyÂ Keywords: Motivation, Attitude, Customer Loyalty